Legal Culture in Protecting Batik Motif Intellectual Property: Indonesia-Malaysia Small Business Comparison - Mulyani, Sri; Kusumaningrum, Anggraeni Endah; Sukmariningsih, Retno Mawarini; Ahamad, Haniff (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Batik, as a national creation, is not only owned by Indonesia but also Malaysia with its own characteristics, giving rise to the need to protect the intellectual property of batik motifs amidst the potential for its preservation. The purpose of this study is to determine and compare the legal culture of small business actors in protecting innovative intellectual property batik motifs in Malaysia and Indonesia. The research method uses a comparative study with data collection through field observations in international community service programs, focus group discussions, question and answer discussions with batik artisans, direct visits to the Selangor Craft Industry Malaysia, and interviews with small business actors at workshop locations. The main findings indicate that the legal culture in Selangor Malaysia and Indonesia tends to not register copyrighted works of batik motifs, hampered by economic factors. The conclusion of the study underscores the importance of intellectual property legal protection to prevent preservation, with the formation of a strong legal culture can increase innovation, competitiveness, and income opportunities through licensing.